2018
DOI: 10.1111/spol.12412
|View full text |Cite
|
Sign up to set email alerts
|

“A game of two halves?” Understanding the process and outcomes of English care home closures: Qualitative and quantitative perspectives

Abstract: With care services increasingly delivered via a market there is always a risk that care homes could fail financially or struggle in terms of quality, ultimately having to close.When this happens, the received wisdom is that subsequent relocation can be detrimental to the health and well-being of older residents (possibly even culminating in increased mortality). However, there is very little formal evidence in the United Kingdom (UK) or beyond to guide policymakers and local leaders when undertaking such sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…ageing where the person has lived so far, has been promoted. The idea to deinstitutionalize long-term care for dependent older people shifts the responsibility of creating the housing and assisting infrastructure to municipalities, which are responsible for addressing the housing needs of sensitive groups (GLASBY and ROBINSON 2019) Creating a housing infrastructure that is well adapted to the needs of seniors will make self-care possible for at least some of themto, and in the case of people with a low level of independence, to provide secure and appropriate care at their homes.…”
Section: Introductionmentioning
confidence: 99%
“…ageing where the person has lived so far, has been promoted. The idea to deinstitutionalize long-term care for dependent older people shifts the responsibility of creating the housing and assisting infrastructure to municipalities, which are responsible for addressing the housing needs of sensitive groups (GLASBY and ROBINSON 2019) Creating a housing infrastructure that is well adapted to the needs of seniors will make self-care possible for at least some of themto, and in the case of people with a low level of independence, to provide secure and appropriate care at their homes.…”
Section: Introductionmentioning
confidence: 99%
“…Through care home closures, financialisation can effectively lead to the eviction of some of the most vulnerable members of society. Research has found “significant” and “inevitable” distress among residents during care home closures, who experienced a sense of confusion, sadness, and loss, while staff faced stress linked to uncertainty about their jobs (Glasby et al., 2019). Home closures can destroy relationships among carers and residents based in particular homes and require additional effort to form connections in new settings; they may place strain on relatives and friends if residents move to a new home at a greater distance from their community; and the relocation of services can require care staff to commute longer distances (union officials).…”
Section: Liquid Home: Care In a Financialised Environmentmentioning
confidence: 99%
“…Carroll and Qualls [39] looked at the psychological aspect of the change of residence, discussing the stages of adaptation to such a change. Glasby et al [40] raised the issue of the consequences of the closure of an institution where elderly people lived.…”
Section: Overview Of Existing Studiesmentioning
confidence: 99%
“…This is the so-called "silver economy". The concept of the "silver economy" originates from Japan and its basic assumption was to focus on the needs of seniors [40][41][42]. The idea of the silver economy assumes the creation of products and services for people over 50 and the implementation of trade agreements and contracts between economic entities that will help to adapt to the employment of increasingly older people [43,44].…”
Section: Silver Economy and Housing For Seniorsmentioning
confidence: 99%